GROWTH HORMONE GENE GENOTYPING BY Msp I RESTRICTION ENZYME AND PCR-RFLP METHODS IN ACEH CATTLE BREED AT INDRAPURI DISTRICT OF ACEH PROVINCE - Putra, W.P.B.; Hartatik, T.; Sumadi, S. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The objective of this research was to identify growth hormone (GH) genes genotype in selectedAceh cattle at Indrapuri’s Breeding and Forage Centre (IBFC) of Aceh Cattle. Fourty one cattleconsisting of 21 male and 20 female cattle were used in this study. The genomic DNA was extractedfrom blood using Sambrook et al. (1989) methods. Polymerase Chain Reaction - Restriction FragmentLength Polymorphism (PCR-RFLP) and mehod of sequencing was used to detect MspI site on GH gene.Based on sequencing results, it can be concluded that all cattle were monomorphism. The frequency ofTT genotype were 1.00 and same as T allele frequency. The transition of C (cytosine) into T (thymine)on 1548 bp caused the lost of restriction site.